Preservação da fertilidade no doente oncológico pediátrico - Ferreira,Maria do Pilar (2020)
The incidence of pediatric cancer has been increasing, but the improvement in survival rates contributed to the growing number of survivors of reproductive age. Oncological treatments can affect fertility therefore, all patients diagnosed with cancer should be informed about the risks of infertility and advised by a multidisciplinary team on the multiple fertility preservation techniques: before puberty or urgency in starting oncological treatment ovarian or testicular tissue cryopreservation are the ones available, although experimental; after puberty, oocyte and sperm cryopreservation are the techniques recommended. The authors present a review of the literature on this subject.